How clean are electric vehicles? Evidence-based review of the effects of electric mobility on air pollutants, greenhouse gas emissions and human health. (July 2018) - Requia, Weeberb J.; Mohamed, Moataz; Higgins, Christopher D.; Arain, Altaf; Ferguson, Mark
Abstract: There is a growing need for a broad overview of the state of knowledge on the environmental aspects of Electric Vehicles (EVs), which could help policymakers in the objective of making road transportation more sustainable and environmental friendly. This study provides a comprehensive review of the effects of EVs adoption on air quality, greenhouse gas emissions, and human health. Specifically, we (i) synthesized relevant published literature related to environmental implication of EVs, (ii) quantitatively evaluated the effect of EVs on environment and human health, and (iii) identified research gaps and recommend future research areas for the adoption of EVs and their benefits to society. We assessed in total 4734 studies and selected 123 articles of more detailed review, with 65 articles fulfilling the inclusion criteria. The studies reviewed consistently showed reductions in greenhouse gas emissions and emissions of some criteria pollutants. Particularly on PM and SO2, the increases or decreases are very dependent on the context. Overall, the positive benefits of EVs for reducing greenhouse gas emissions and human exposure depends on the following factors: (i) type of EV, (ii) source of energy generation, (iii) driving conditions, (iv) charging patterns, (v) availbailty of charging infrastructure, (vi) govermnat policies, and (vii) climate of a regions. This study provides a comprehansive analysis and review on the benefits of electric mobility. Graphical abstract: Image 1 Highlights: We assessed 4734 studies and selected 123 articles for more detailed review. Most of the studies were carried out in the United States or China. EVs may have a role in reducing air pollution and its consequences for health.